2022
DOI: 10.3389/fnins.2022.1008752
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis identifies shared biological foundations between ischemic stroke and Alzheimer’s disease

Abstract: AimAlzheimer’s disease (AD) and ischemic stroke (IS), two major neurological diseases, are suggested to be associated in clinical and pathophysiological levels. Previous studies have provided some insights into the possible genetic mechanisms behind the correlation between AD and IS, but this issue is still not clear. We implemented transcriptomic analysis to detect common hub genes and pathways to help promote the understanding of this issue.Materials and methodsFour gene expression profiling datasets (GSE165… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, protein-drug interaction analysis revealed that PDE9A interacts with drugs such as caffeine, γ-glutamyl glycine, and 3-isobutyl-1-methyl-7H-xanthine. Through the PPI and network topology analysis for the common DEGs, Liu W. et al (2022) identified hub genes RPS3, RPS15, PSMB6, MRPL17, and MRPL24 of AD and IS.…”
Section: Identification Of Shared Candidate Biomarkers Between Ad And...mentioning
confidence: 99%
“…Furthermore, protein-drug interaction analysis revealed that PDE9A interacts with drugs such as caffeine, γ-glutamyl glycine, and 3-isobutyl-1-methyl-7H-xanthine. Through the PPI and network topology analysis for the common DEGs, Liu W. et al (2022) identified hub genes RPS3, RPS15, PSMB6, MRPL17, and MRPL24 of AD and IS.…”
Section: Identification Of Shared Candidate Biomarkers Between Ad And...mentioning
confidence: 99%
“…The data were quantile normalized, and the differential expressed miRNAs (DEmiRNAs), mRNAs (DEmRNAs), and lncRNAs (DElncRNAs) between the IS and control samples were identified using R's limma package (v3.52.0) [19]. The P < 0.05, |log 2-fold change (FC)| > 0.5 were selected as cut-off criteria in identifying DEmRNAs and DEmiRNAs by previously reported methods [10,21,[28][29][30], and |log 2-fold change (FC)| > 1 was selected to identify DElncRNA [31,32]. Thereafter, volcano plots of DEmiRNAs, DElncRNAs, and DEmRNAs were generated using the ggplot2 package (v3.3.6) [33].…”
Section: Differential Expression Analysismentioning
confidence: 99%
“… 116 Recently, Liu and coworkers identified 74 differentially expressed genes and largely immune‐related pathways shared in AD pathology and ischemic stroke. 117 …”
Section: The Heart Of the Problem: Atherosclerosis Versus Arterioscle...mentioning
confidence: 99%